Parental time with children: Do job characteristics make a difference? (Research Paper No. 44). - Baxter, Jennifer (My University, 2009)
To contribute to our understanding of how paid work and family time interact, this paper examines how characteristics of parental paid employment are associated with differences in parent-child time. With an increased participation of mothers in paid employment, especially in part-time work, and an increase in non-standard paid work hours, it is important to understand how such factors are related to a loss of time shared between parent and child. The analysis uses the time use diaries of two cohorts of children: the infant cohort (aged 3-19 months old at interview) and the 4-5 year old cohort, collected in the first wave (2004) of the Longitudinal Study of Australian Children (LSAC). Very clear differences emerged. For example, children spent more time with their mother overall and spent more time with parents on the weekend than on weekdays. Association with parental hours of paid work, evening or night work, weekend work, flexibility of hours, job contract and occupation status were explored. Hours of paid work had the strongest relationships with parent-child time, although the frequency of weekend work also explained some of the variation.
Keywords: Employment; Families -- Parents and Parenting; Families; Labour market; Families and relationships; Families; Employment; Parents and Parenting; Employment and unemployment; Families and relationships